2015
DOI: 10.1007/s00408-015-9688-8
|View full text |Cite
|
Sign up to set email alerts
|

Profibrosing Effect of Angiotensin Converting Enzyme Inhibitors in Human Lung Fibroblasts

Abstract: Results show that ACEis and losartan could play a profibrosing role by inducing the overexpression of molecules such TGF-β1 and Collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…The present study showed the down-regulation of TGF-β in bone of ORX mice, which was in consistent with early study [39]. The increase in TGF-β expression in response to captopril treatment was found in ORX mice in this study, and the similar action of captopril on TGF-β was also reported in human lung fibroblasts [40]. Our study indicated that the regulation of captopril on TNF-α and TGF-β might be involved in its protective effects on bone tissue of ORX mice.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed the down-regulation of TGF-β in bone of ORX mice, which was in consistent with early study [39]. The increase in TGF-β expression in response to captopril treatment was found in ORX mice in this study, and the similar action of captopril on TGF-β was also reported in human lung fibroblasts [40]. Our study indicated that the regulation of captopril on TNF-α and TGF-β might be involved in its protective effects on bone tissue of ORX mice.…”
Section: Discussionsupporting
confidence: 93%
“…Initially, concentrations of 10 mM were used for losartan as pretreatment. 37 However, under these conditions there was a decrease in cellular viability of fibroblasts, so a lower concentration (1 mM) of the drug was applied, which maintained viable cells (data not shown). Concentration of 1 mM of losartan was also used in previous studies with different cell types.…”
Section: Discussionmentioning
confidence: 95%
“…Use of AT1R antagonist (losartan) did not interfere with IL‐1β‐induced mRNA for AT1R or other investigated RAS components (Mas receptor, ACE and ACE‐2 enzymes) in both fibroblast subtypes. Initially, concentrations of 10 μM were used for losartan as pretreatment 37 . However, under these conditions there was a decrease in cellular viability of fibroblasts, so a lower concentration (1 μM) of the drug was applied, which maintained viable cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ACEI and ARB have recently been shown to provide protection against chronic lung injuries by inhibiting pulmonary fibrosis in end‐stage ARDS and Idiopathic Pulmonary Fibrosis (IPF) 25,26 . In addition, a prospective study suggested that 6 months of ACEI exposure could effectively improve lung function indexes through the enhancement of respiratory muscle strength in patients with heart failure 27 .…”
Section: Discussionmentioning
confidence: 99%